Collective Identity and Promotion Prospects in the South Korean Army. (April 2014) - Kim, Insoo; Crabb, Tyler
This study examines how collective identity based around military school ties influences an individual officer's achievement in the military. The central premise of this study is that if collective identity can form the basis for fragmented social networks in the South Korean officer corps, it can result in different opportunities for members within different networks. The results presented here demonstrate that collective identities are important explanatory factors to account for this exchange of social resources. All else being equal, the exchange of instrumental and material resources is more likely between military officers who graduated from the same civilian or military school.